2017
DOI: 10.4095/305902
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of ecological functions on the Flemish Cap (northwest Atlantic)

Abstract: Ecosystem Approaches to Fisheries (EAF) are seen as essential for sustaining fish stocks and fisheries over the long-term, and require the integration of ecosystem components, typically through multivariate and multifunction analyses. Large scale functional maps showing the distribution of organisms with particular biological traits (e.g., deposit feeders, filter feeders, biogenic engineers, carbon sequesters, etc.) can provide a detailed spatial framework for incorporating benthic ecosystem function into an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Large gorgonian corals also play an important role as structure formers. However, trawl catches have shown that in the sampling area they do not form large habitats that have a significant influence on diversity (Murillo et al, ). However, they could also be more important on hard bottoms not sampled by trawl gears.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large gorgonian corals also play an important role as structure formers. However, trawl catches have shown that in the sampling area they do not form large habitats that have a significant influence on diversity (Murillo et al, ). However, they could also be more important on hard bottoms not sampled by trawl gears.…”
Section: Discussionmentioning
confidence: 99%
“…Seven fixed environmental variables and 45 summary statistics of 15 other environmental variables and fishing effort were used as predictors (Appendix , Table S5.2). These are the same predictors used previously by Murillo et al () to map the ecological diversity based on the number of species and will allow us to evaluate the relationship between functional and species diversity in the Flemish Cap area. Specific details on the methods used for the spatial interpolation of these variables are documented in Guijarro et al () and sources and spatial resolution provided in Appendix , Table S5.2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation